High-entropy-alloy nanoparticles synthesized by laser metallurgy using a multivariate MOF. (18th August 2022) - Yan, Wei; Jiang, Haoqing; Yi, Wendi; Zhao, Chengbin; Xia, Yucong; Cong, Hengjiang; Tang, Lin; Cheng, Gary J.; He, Jianhua; Deng, Hexiang
Abstract : The illustration of the fabrication of nanoalloys by laser nanometallurgy using multivariate MOF as precursor. Abstract : We report the synthesis of multivariate MOFs with combinations of metal ions, including Mn 2+, Fe 3+, Co 2+, Ni 2+, Cu 2+ and Zn 2+ . The permanent porosity and the evenly distributed metal components make these porous crystals ideally suited for the synthesis of alloy nanoparticles. Using a laser, these MOFs are converted in air to alloy nanoparticles of binary (FeNi, FeCo), ternary (FeCoNi) and high-entropy-alloys with quinary (MnFeCoNiCu, MnFeCoNiZn) metals. One member, FeNi alloy nanoparticles with a narrow particle size distribution around 7 nm, shows a low overpotential of 282 mV at a current density of 10 mA cm −2 in the oxygen evolution reaction (OER), better than those of the single metal counterparts. This demonstrates the possibility of using MOFs to produce alloy nanoparticles with multiple metal components by a laser.